Superelevation of Road Curves: Influence on Vehicles Fuel Consumption - Coiret , Alex; Vandanjon, Pierre-Olivier (Transportation Development Research, 2026)
Transport systems are primarily designed to address mobility and safety concerns. Today, energy consumption must also be taken into account in infrastructure design and operation, as environmental issues and tensions in oil production continue to intensify. For road transport, infrastructure requires energy for its construction, maintenance, and use. During the use phase, previous studies have assessed the influence of road texture, longitudinal slopes, and curvature on vehicle consumption. In this study, superelevation in curves is investigated as an additional parameter that may affect vehicle energy consumption. This investigation is first introduced using a simplified two-wheel model, showing a computed reduction in rolling resistance of 3% to 9% depending on cases. Full-scale experiments were then conducted using similar parameter ranges, with an instrumented passenger car on a curved road section featuring a continuous crossfall varying from 0 to 40%, and at three travel speeds: 80, 110, and 120 km/h. Experimental measurements confirm the numerical approach, with consumption reductions of up to 10% achieved for a light vehicle on a curve with optimal crossfall. The aim of this research is not to promote the design of all roads with high superelevation, which could be unsafe in most cases, but rather to contribute empirical knowledge to refine numerical consumption models. However, in specific situations such as high-speed highways, intermediate or high crossfall could be considered, provided that appropriate driver warnings are implemented or that advanced driving assistance systems become widespread. Future perspectives are discussed, taking into account other road requirements such as safety